2021
DOI: 10.3390/medicina57121327
|View full text |Cite
|
Sign up to set email alerts
|

Immune Response after SARS-CoV-2 Vaccination in Kidney Transplant Patients

Abstract: Background and Objectives: The prospective study was conducted to evaluate humoral and cellular immune responses after two doses of BNT162b2 (Pfizer-BioNTech) vaccine and possible relation with other factors (medication, etc.) in kidney transplant patients. Materials and Methods: Out of 167 vaccinated patients, 136 agreed to a follow-up visit three to six weeks after vaccination. Results: Only 39 patients (29%) developed antibody response against SARS-CoV-2 (≥35.2 binding antibody units (BAU)/mL) after full va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 39 publications
(43 reference statements)
3
15
0
1
Order By: Relevance
“…Studies have shown that the use of mycophenolate mofetil significantly hampers the seroconversion after vaccination in RTRs (5,20). All our patients were on mycophenolate mofetil at the time of sampling.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Studies have shown that the use of mycophenolate mofetil significantly hampers the seroconversion after vaccination in RTRs (5,20). All our patients were on mycophenolate mofetil at the time of sampling.…”
Section: Discussionmentioning
confidence: 95%
“…The poor seroconversion is expected in RTRs because of an immunocompromised state because of immunosuppressions like calcineurin inhibitors, mycophenolate mofetil, and corticosteroids. Studies have shown that the use of mycophenolate mofetil significantly hampers the seroconversion after vaccination in RTRs ( 5 , 20 ). All our patients were on mycophenolate mofetil at the time of sampling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Vaiciuniene et al reported 6 biopsy-confirmed ARs in 167 fully vaccinated KT recipients with mRNA vaccine in 9 mo follow-up. 2 Our results provided the safety profile of the whole-virus inactivated COVID-19 vaccine in KTs, suggesting that more intensive monitoring of graft function after vaccination was necessary. Notably, due to lack of matched control group and ascertainment bias, it remains unclear whether there is casual association between renal complications and vaccination.…”
mentioning
confidence: 70%
“…Prevaccination eGFR, mL/min/1.73m 2 Boyarsky et al reported that 1 of 176 experienced AR after receiving 2 doses of mRNA vaccines. 5 Vaiciuniene et al reported 6 biopsy-confirmed ARs in 167 fully vaccinated KT recipients with mRNA vaccine in 9 mo follow-up.…”
Section: Events (Proportion)mentioning
confidence: 99%